TIME-BASED CHANGES IN ESSENTIAL OIL CONTENTS AND COMPONENTS OF ENGLISH LAVENDER (Lavandula angustifolia MILL.) AFTER FOLIAR APPLICATION OF GIBBERELLIC ACID (GA3) - Mehmet Ugur YILDIRIM; Ahmet IZMIRLI (Journal of Animal and Plant Sciences, 2023)
Lavender (Lavandula angustifolia Mill. family Lamiaceae) is a perennial and highly drought tolerant plant species. It grows well on calcareous slopes, and produces a fragrant essential oil. The aim of study was to evaluate foliar application of gibberellic acid (GA3) and delaying harvesting for different durations on essential oil and components of English lavender after foliar treatment with 0, 200, 400 and 600 mg l-1 gibberellic acid (GA3). Clevenger apparatus-based water-vapor distillation method was used to determine essential oil and its components by GC-MS. The experiment was established in split plots in randomized complete block design with two factors and 3 replications. The main plots were formed at harvest time and the sub-plots were created by GA3 applications. Statistical analyzes were made using MSTAT-C package program. When the GA3 doses and harvest times interaction were evaluated together, the average essential oil yield of the harvested lavender flowers ranged 6.20 to 8.20 % showing the prominent influence of the concentration of GA3 and delay in harvesting (in hours) on concentrartration of alkaloids. More than 50 components were identified, the most important among these was 1.8-cineole, linalool, camphor, borneol, lavandulol, and terpinene-4-ol. The amount of linalool, which improves the quality of the essential oil ranged 34.49-38.75%. The minimum and the maximum essential oil values were noted from the flowers harvested after 30 hours (control treatments), and 54 hours from 400 mg l-1 GA3 treated plants in the same order. However, essential oil contents showed a slight decrease at higher GA3 treatments and prolonging duration of harvest after respective GA3 treatments. GA3 treatments enhanced the quantity of essential oil substantially, and the optimal dose was determined as 400 mg l-1 GA3 on samples harvested after 54 hours following application. The results further showed that the quantities of essential oil's primary components varied according to harvest time.
Keywords: Aromatic plant; camphor; flower; linalool; plant growth regulator